Interlanguage Errors Found In Islamic English Speech TextsIn "Contoh-Contoh Pidato 3 Bahasa" - Kurniawati, Ari, Prof. Dr. Endang Fauziati, M. Hum, Nur Hidayat, M.Pd (2014)
This study aims at de cribing the interlanguage errors found in the texts of Islamic English speech in Contoh-Contoh Pidato 3 Bahasa; identifying types of errors in morphological level, syntactical level, and discourse level; describing frequency of each type of errors; explaining dominant types of error; identifying sources of errors and explaining the pedagogical implication in devising the appropriate English reading materials. The type of this research is descriptive qualitative. Elicitation technique and documentation are methods to collect the data. There are three steps to collect the data, namely: the writer gets the data from the texts of Islamic English speech, the writer classifies the data. The collected data are analyzed by using James classification of errors theory, Slamet's frequency types of error and Brown's sources of error theory.The results of the research show that the texts of Islamic English speech contain 247 errors from 107 pages. The writer finds that from 247 data, there are three classification of error based on linguistic category and surface strategy taxonomy. There are morphological errors consist of 34.8% including: bound morpheme 15.6%, word 22.9%, code switching 0.4%, literal translation 0.8%, false friend 4%. Syntactical errors consist of 61.5% including: phrase 13.7%, subordinate clause 3.6%, sentence 4, 4%, tenses16.9%, BE 14%, article 2.4%, pronoun 2%, preposition 3.2%. Discourse errors onsist of 3.6%, including: conjunction 2.4%, reference 0.4%, and ellipsis 0.8%. It is derived from 57 types of errors; the highest frequency is errors in word spelling 37 or 14.9%. The reseacher also finds 2 dominant sources of error, namely: interlingual and intralingual transfer.